A Markov chain Monte Carlo model of mechanical-feedback-driven progressive apical constrictions captures the fluctuating collective cell dynamics in the Drosophila embryo - Gao, Guo–Jie J.; Holcomb, Michael C.; Thomas, Jeffrey H.; Blawzdziewicz, Jerzy (Frontiers in Physics, 2022)
Communication via mechanical stress feedback is believed to play an important role in the intercellular coordination of collective cellular movements. One such movement is ventral furrow formation (VFF) in the Drosophila melanogaster embryo. We previously introduced an active granular fluid (AGF) model, which demonstrated that cellular constriction chains observed during the initial phase of VFF are likely the result of intercellular coordination by tensile mechanical stress feedback. Further observation of individual cellular dynamics motivated us to introduce progressive constrictions and Markov chain Monte Carlo (MCMC) based fluctuation of particle radii to our AGF model. We use a novel stress-based Voronoi tessellation method to translate the anisotropic network of highly polydisperse, axisymmetric force centers into a confluent cellular layer. This allows us to apply a similar means of analysis to both live and simulated embryos. We find that our enhanced AGF model, which combines tensile mechanical stress feedback and individual cellular fluctuations, successfully captures collective cell dynamics.